Household Allocation of Time and Religiosity: Replication and Extension - Ehrenberg, Ronald G. (Journal of Political Economy, 1977)
Stephen Long and Russell Settle's (1977) empirical tests of the economic theory of religiosity presented by Corry Azzi and myself (1975) in this Journal tend to be less supportive of our theory than were our original results. As such, I welcome the opportunity to trot out some further replications and extensions that I have conducted and I leave it to the reader to judge the relative merits of the two new contributions.